Sleep-disordered breathing and pregnancy: potential mechanisms and evidence for maternal and fetal morbidity - Izci-Balserak, Bilgay (2010)
PURPOSE OF REVIEW: This article reviews current data on pathophysiologic mechanisms by which sleep-disordered breathing during pregnancy may cause harm, and explores biological pathways for associated adverse maternal and fetal outcomes, especially pregnancy-induced hypertension and gestational diabetes. RECENT FINDINGS: Accumulating data indicate that snoring and sleep apnea during pregnancy are likely to increase the risk for gestational hypertension and preeclampsia. Several new studies have observed that sleep-disordered breathing and short sleep duration also increase the risk of gestational diabetes, similar to observations in the general population. There are varying levels of emerging evidence for potential mechanisms, including oxidative stress, increased sympathetic activity and inflammation, adipokine levels and insulin resistance, linking sleep-disordered breathing events during pregnancy to adverse outcomes. SUMMARY: Sleep-disordered breathing and adverse maternal–fetal outcomes such as preeclampsia and gestational diabetes share a number of mechanistic pathways, and growing data in pregnant women indicate that snoring and sleep apnea increase the risk of these and other complications for both the mother and the fetus. Nevertheless, direct evidence of the pathophysiologic mechanisms by which sleep-disordered breathing during pregnancy exerts negative effects remains sparse.